Peucela acutativalva Qi & Li, 2020 (Lepidoptera: Pyralidae): An addition to the Indian fauna - Lotani, Narendra Singh; Negi, Chandra Singh (Zootaxa, 2024)
Peucela acutativalva Qi & Li, 2020 is reported from the Kumaon Himalaya, Uttarakhand, India. The specimens examined are slightly different from those described by Qi et al. (2020). These differences are discussed.